Extremal properties of nondifferentiable convex functions on euclidean sets of combinations with repetitions - Emets, O. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
A general approach is suggested for studying extremal properties of nondifferentiable convex functions on Euclidean combinatorial sets. On the basis of this approach, by solving the linear optimization problem on a set of combinations with repetitions, we obtain estimates of minimum values of convex and strongly convex objective functions in optimization problems on sets of combinations with repetitions and establish sufficient conditions for the existence of the corresponding minima.